2021 29th European Signal Processing Conference (EUSIPCO) 2021
DOI: 10.23919/eusipco54536.2021.9616232
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Trajectory Planning for Multi-Rotor UAV Relays with Tilt and Antenna Orientation Variations

Abstract: Multi-rotor Unmanned Aerial Vehicles (UAVs) need to tilt in order to move; this modifies the UAV's antenna orientation. We consider the scenario where a multi-rotor UAV serves as a communication relay between a Base Station (BS) and another UAV. We propose a framework to generate feasible trajectories for the multi-rotor UAV relay while considering its motion dynamics and the motion-induced changes of the antenna orientation. The UAV relay's trajectory is optimized to maximize the end-to-end number of bits tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Note, that overshooting has to be re-defined from the previous sign-based equation (20) to account for the fact that in higher dimensions, the state can move outside the line between the original state and the true desired state. Therefore, overshooting will be defined as a change from the original state po to a new state pn , where its orthogonal projection onto the line connecting po and the desired target ph (measured with measurement noise covariance C) falls beyond the desired target from the perspective of the original position, i.e.…”
Section: Extension To R 3 × Smentioning
confidence: 99%
See 1 more Smart Citation
“…Note, that overshooting has to be re-defined from the previous sign-based equation (20) to account for the fact that in higher dimensions, the state can move outside the line between the original state and the true desired state. Therefore, overshooting will be defined as a change from the original state po to a new state pn , where its orthogonal projection onto the line connecting po and the desired target ph (measured with measurement noise covariance C) falls beyond the desired target from the perspective of the original position, i.e.…”
Section: Extension To R 3 × Smentioning
confidence: 99%
“…Each of these values is provided with the covariance of its observation noise [18]. Additionally, the system can provide robotic units with unique retrievable identities, and even possesses limited data communication capabilities without radio transmission [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a clear need for safe and practical setups that enable more efficient maintenance and inspection procedures in electrical power lines, thereby reducing risks and costs for distribution companies. Multiple solutions have been investigated in the literature for automating this task [4], but the most promising and flexible option is to use Unmanned Aerial Vehicles (UAVs), as they are capable of supporting inspection at different levels [7], [8]. For instance, UAVs can monitor places of difficult access making the inspection operations faster and more effective.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the research and commercial interest on Unmanned Aerial Vehicles (UAVs) has exploded as demonstrated by the growing number of applications, such as infrastructure monitoring [1], aerial filming [2], surveillance and search and rescue missions [3] and wireless communications [4]. Most of these applications require UAVs with visual sensors and with certain autonomy that enable them to rapidly react in dynamic environments to successfully accomplish their mission.…”
Section: Introductionmentioning
confidence: 99%